Induced Pluripotent Stem Cells From Subjects With Primary Sclerosing Cholangitis Develop a Senescence Phenotype Following Biliary Differentiation. Issue 2 (25th August 2021) - Jalan‐Sakrikar, Nidhi; De Assuncao, Thiago M.; Navarro‐Corcuera, Amaia; Hamdan, Feda H.; Loarca, Lorena; Kirkeby, Lindsey A.; Resch, Zachary T.; O'Hara, Steven P.; Juran, Brian D.; Lazaridis, Konstantinos N.; Rosen, Charles B.; Heimbach, Julie K.; et al.
Abstract : Primary sclerosing cholangitis (PSC) is a chronic fibroinflammatory disease of the biliary tract characterized by cellular senescence and periportal fibrogenesis. Specific disease features that are cell intrinsic and either genetically or epigenetically mediated remain unclear due in part to a lack of appropriate, patient‐specific, in vitro models. Recently, our group developed systems to create induced pluripotent stem cell (iPSC)‐derived cholangiocytes (iDCs) and biliary epithelial organoids (cholangioids). We use these models to investigate whether PSC cholangiocytes are intrinsically predisposed to cellular senescence. Skin fibroblasts from healthy controls and subjects with PSC were reprogrammed to pluripotency, differentiated to cholangiocytes, and subsequently grown in three‐dimensional matrigel‐based culture to induce formation of cholangioids. RNA sequencing (RNA‐seq) on iDCs showed significant differences in gene expression patterns, including enrichment of pathways associated with cell cycle, senescence, and hepatic fibrosis, that correlate with PSC. These pathways also overlapped with RNA‐seq analysis on isolated cholangiocytes from subjects with PSC. Exome sequencing on the subjects with PSC revealed genetic variants of unknown significance in the genes identified in these pathways. Three‐dimensional culture revealed smaller size, lack of a central lumen, and increased cellular senescence in PSC‐derived cholangioids. Congruent with this, PSC‐derived iDCs showed increased secretion of the extracellular matrix molecule fibronectin as well as the inflammatory cytokines interleukin‐6, and chemokine (C‐C motif) ligand 2. Conditioned media (CM) from PSC‐derived iDCs more potently activated hepatic stellate cells compared to control CM. Conclusion: We demonstrated efficient generation of iDCs and cholangioids from patients with PSC that show disease‐specific features. PSC cholangiocytes are intrinsically predisposed to cellular senescence. These features are unmasked following biliary differentiation of pluripotent stem cells and have functional consequences in epithelial organoids. Abstract : Biliary differentiation of Induced Pluripotent Stem Cells from subjects with Primary Sclerosing Cholangitis unmasks their senescence phenotype and ability to activate hepatic stellate cells.